Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11145-010-9227-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive skills and literacy performance of Chinese adolescents with and without dyslexia

Abstract: The present study sought to identify cognitive abilities that might distinguish Hong Kong Chinese adolescents with dyslexia and to assess how these abilities were associated with Chinese word reading, word dictation, and reading comprehension. The cognitive skills of interest were morphological awareness, visual-orthographic knowledge, rapid naming, and verbal working memory. A total of 90 junior secondary school students, 30 dyslexic, 30 chronological age controls, and 30 reading level controls was tested on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 68 publications
12
59
0
Order By: Relevance
“…It is possible that a semantic task that was more difficult or that tapped into a different morphological process would show differences between dyslexic and typical readers. Indeed, previous research shows that certain morphological tasks, especially those requiring morpheme parsing from words with two or more morphemes, tend to be more difficult for Chinese children with dyslexia (Chung, Ho, Chan, Tsang, & Lee, 2011; Shu et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a semantic task that was more difficult or that tapped into a different morphological process would show differences between dyslexic and typical readers. Indeed, previous research shows that certain morphological tasks, especially those requiring morpheme parsing from words with two or more morphemes, tend to be more difficult for Chinese children with dyslexia (Chung, Ho, Chan, Tsang, & Lee, 2011; Shu et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Most important for the question of writing effects on reading, character connections to both phonology and meaning depend crucially on establishing a high quality representation of the written character form. Indeed, some studies suggest that orthographic awareness, rather than phonological awareness, is the most predictive variable for Chinese reading achievement [Chung et al, 2010;Siok and Fletcher, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies (e.g. Chung, Ho, Chan, Tsang, & Lee, ; Shu et al ., ), children's ability to distinguish among meanings of homophones and morpheme discrimination was found to contribute significantly to reading failure in Chinese (e.g. Chung et al ., ; Shu et al ., ).…”
mentioning
confidence: 99%
“…Chung, Ho, Chan, Tsang, & Lee, ; Shu et al ., ), children's ability to distinguish among meanings of homophones and morpheme discrimination was found to contribute significantly to reading failure in Chinese (e.g. Chung et al ., ; Shu et al ., ). For example, Shu, McBride‐Chang, Wu and Liu () demonstrated that morphological awareness was one of the best discriminators for children with and without dyslexia.…”
mentioning
confidence: 99%